2013
DOI: 10.1590/0037-868212382013
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax malaria: related factors to severity in the State of Maranhão, Brazil

Abstract: Introduction: Malaria caused by Plasmodium vivax species has shown signs of severity, recorded with increasing frequency in the medical literature. This study aimed to characterize the signs of severe malaria by Plasmodium vivax in the State of Maranhão, Brazil. Methods: A descriptive cohort study of patients assisted in the field and a historical and concurrent study of a series of cases among hospitalized patients were undertaken to identify the clinical and laboratory signs of severity. Results: A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
(21 reference statements)
1
12
0
6
Order By: Relevance
“…One percent of the cases were caused by other species. Noteworthy, P. vivax has been increasingly associated with severe malaria, leading to complications that include respiratory distress, shock, and anemia [59,60,61,62]. In Brazil, the cases of malaria are seldom caused by P. malariae, and those are usually restricted to speci c Amazon regions and its surroundings [58,63].…”
Section: Discussionmentioning
confidence: 99%
“…One percent of the cases were caused by other species. Noteworthy, P. vivax has been increasingly associated with severe malaria, leading to complications that include respiratory distress, shock, and anemia [59,60,61,62]. In Brazil, the cases of malaria are seldom caused by P. malariae, and those are usually restricted to speci c Amazon regions and its surroundings [58,63].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been shown that this so-called benign malaria can result in severe presentation with multiple organ dysfunction and life-threatening disease. The majority of severe vivax malaria cases have been reported in India [1-4], but many cases occurred in other countries where there is active transmission, such as Ethiopia [5], Sudan [6], Cambodia [7], Colombia [8], and Brazil [9-12]. Criteria for diagnosing severe vivax malaria, as opposed to severe falciparum malaria, are still not clearly defined, since some biological features of these two parasites are different, and in the meantime the WHO definition for severe falciparum malaria is used [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although the State of Piauí is situated outside the Amazon, it borders Maranhão and Tocantins, two states located in the Amazonian region. These two states have active transmission of malaria (11) (12) .…”
mentioning
confidence: 99%